Hepatitis C as a Prognostic Indicator among Noncirrhotic Patients Hospitalized with Alcoholic Hepatitis - Paul J Thuluvath; Eric Ahn; Geoffrey C Nguyen (Canadian Journal of Gastroenterology)
OBJECTIVE: A nationwide analysis of alcoholic hepatitis (AH) admissions was conducted to determine the impact of hepatitis C virus (HCV) infection on short-term survival and hospital resource utilization.